Preservice Teachers' Experiences of "America Reads" Research - Penny L. Beed; David Landis; Charline Barnes; Kari Benson; Kim Willms; Amy Zidlicky (Networks: An Online Journal for Teacher Research, 1999)
This article has two purposes. First, we want to make visible the experiences of undergraduate preservice teacher researchers who collaborated with university faculty to conduct three research studies of an America Reads Literacy Tutoring Program. Our second purpose is to offer evidence from the preservice teachers' research logs, comments and reflections that supports or challenges current discussions about the effects of preservice teacher research. The article begins with a brief discussion of the America Reads investigations in which the preservice teachers participated. Next, we discuss the preservice teachers' thoughts about their research experiences. Finally, we explore implications raised by this research.